Mediation and the courts on settlement of disputes: An analysis on legislating court-directed mediation in Malaysia /Christina Ooi Su Siang - Christina Ooi, Su Siang (2017)
Today court-directed mediation practice in Malaysia is not governed by Mediation Act 2012 which came into operation on August 1, 2012. The said Mediation Act 2012 is only applicable to private mediation where mediators are not judges or judicial officers. In the absence of such legislation, judges and judicial officers are mainly guided by Practice Direction No. 5 of 2010 and Rules for Court Assisted Mediation. This study attempts to examine whether court-directed mediation should be legislated in Malaysia to ensure consistency in mediation practice based on one common set of mediation process, governance and standards for all mediators in Malaysia.